Ultrarapid and high-resolution HLA class I typing using transposase-based nanopore sequencing applied in pharmacogenetic testing - Anukul, Nampeung; Jenjaroenpun, Piroon; Sirikul, Chonticha; Wankaew, Natnicha; Nimsamer, Pattaraporn; Roothumnong, Ekkapong; Pithukpakorn, Manop; Leetrakool, Nipapan; Wongsurawat, Thidathip (Frontiers in Genetics, 2023)
Nanopore sequencing has been examined as a method for rapid and high-resolution HLA typing in recent years. We aimed to apply ultrarapid nanopore-based HLA typing for HLA class I alleles associated with drug hypersensitivity including HLA-A*31:01, HLA-B*15:02, and HLA-C*08:01. Most studies have used the Oxford Nanopore Ligation Sequencing kit for HLA typing, which requires several enzymatic reactions and remains relatively expensive, even when samples are multiplexed. Here, we used the Oxford Nanopore Rapid Barcoding kit, which is transposase-based, with library preparation taking less than 1 hour of hands-on time and requiring minimal reagents. Twenty DNA samples were genotyped for HLA-A, -B, and -C; 11 samples were from different ethnicity individuals, and 9 were from Thai individuals. Two primer sets, a commercial set and a published set, were used to amplify the HLA-A, -B, and -C genes. HLA-typing tools that used different algorithms were applied and compared. We found that without using several third-party reagents, the transposase-based method reduced hands-on time from approximately 9 hours to 4 hours, making this a viable approach for obtaining same-day results from 2-24 samples. However, an imbalance in the PCR amplification of different haplotypes could affect the accuracy of typing results. This work demonstrates the ability of transposase-based sequencing to report 6-digit HLA alleles and its potential for race- and population-independent testing at considerably decreased time and cost.